1991
DOI: 10.1002/ajim.4700190403
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive hazards of fire fighting I. Non‐chemical hazards

Abstract: Fire fighters are regularly exposed to chemical and non-chemical agents that have known or suspected adverse effects on reproductive health. Although chemical agents have received some attention, non-chemical hazards such as heat, noise, and physical exertion have only recently been examined for their reproductive effects. There is evidence that heat, noise, and physical exertion may affect various endpoints of reproductive health, including fertility, fetal loss, and growth parameters of the offspring. In par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…Comparing 92 ceramic oven operators with long exposure to high temperatures (37°C, 8 h/day) to 87 controls, it was found that the mean TTP was signi®cantly longer in the exposed group (3.3 vs. 1.3, p 0X05), although semen analysis showed no signi®cant differences, except in sperm velocity (Figa-Talamanca et al, 1992). The TTP for the last pregnancy was not compared between exposed and non-exposed workers (Agnew et al, 1991;Bonde, 1992). The sperm count, motile sperm count, sperm concentration, and the proportion of normalshaped spermatozoa fell within 4 to 6 weeks of the ®rst exposure to heat (31°C to 45°C, 5 h/day) in a subgroup of 10 welders, and increased 4 weeks after cessation of heat exposure in another subgroup of eight welders.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Comparing 92 ceramic oven operators with long exposure to high temperatures (37°C, 8 h/day) to 87 controls, it was found that the mean TTP was signi®cantly longer in the exposed group (3.3 vs. 1.3, p 0X05), although semen analysis showed no signi®cant differences, except in sperm velocity (Figa-Talamanca et al, 1992). The TTP for the last pregnancy was not compared between exposed and non-exposed workers (Agnew et al, 1991;Bonde, 1992). The sperm count, motile sperm count, sperm concentration, and the proportion of normalshaped spermatozoa fell within 4 to 6 weeks of the ®rst exposure to heat (31°C to 45°C, 5 h/day) in a subgroup of 10 welders, and increased 4 weeks after cessation of heat exposure in another subgroup of eight welders.…”
Section: Discussionmentioning
confidence: 98%
“…The sperm count, motile sperm count, sperm concentration, and the proportion of normalshaped spermatozoa fell within 4 to 6 weeks of the ®rst exposure to heat (31°C to 45°C, 5 h/day) in a subgroup of 10 welders, and increased 4 weeks after cessation of heat exposure in another subgroup of eight welders. The TTP for the last pregnancy was not compared between exposed and non-exposed workers (Agnew et al, 1991;Bonde, 1992). Very recently, Tiemessen et al (1996) reported signi®cant Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to heat, resulting in increased scrotal temperature, has been associated with decreased semen quality. 30,31 Hairdressers have been reported to have slightly lower fecundability (probability of conception) than controls, 32 and hairdressing involves exposure to numerous chemicals, some of which have been shown to cause reproductive toxicity in animal studies. 33 A fertility specialist should evaluate both husband and wife to try and pinpoint where the fertility problem(s) lies.…”
Section: Case 3: Infertilitymentioning
confidence: 99%
“…Didymitis causes decreased testicular volume and oligospermia [10]. Being exposed to heat, noise, and physical exercise causes testicular damage and finally terato and oligoasthenospermia [11]. Patients with an STI background have an obvious leukocytospermia, and sufficient primary treatment of STI can prevent delayed complications [12].…”
Section: Introductionmentioning
confidence: 99%